Moderasi beragama melalui pendidikan dan kegiatan sosial: Kontribusi mahasiswa kkm di desa Poncokusumo - Sahrani, Putri (Maliki Interdisciplinary Journal, 2025)
This research aims to explore the contribution of Student Work Lecture (KKM) 83 UIN Malang students in implementing religious moderation through education and social activities in Poncokusumo Village. This village is the location where KKM has been implemented repeatedly, with a focus on strengthening understanding of religious moderation, tolerance and social harmony. Through activities at TPQ Madin Roudlotul Maghfiroh and MI Sunan Muria, KKM students play a role in teaching the values ​​of religious moderation and carrying out social activities such as recitations and mutual cooperation to increase public awareness about the importance of moderate attitudes in religion. This research uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation. The research results show that the educational and social approach applied by KKM 83 students contributes positively to increasing community understanding of religious moderation and strengthening the practice of tolerance in Poncokusumo Village. Thus, education and social activities can be effective means of realizing inclusive and harmonious religious moderation in society.